ANALISIS GAYA KEPEMIMPINAN KEPALA BADAN PENELITIAN DAN PENGEMBANGAN DAERAH PROVINSI SULAWESI TENGAH - Hadidjah, Sitti (Katalogis, 2013)
This research aimed to analyze the leadership style of the head of the provincial research and Development office of Central Sulawesi (Balibangda) and the inhibiting factors of his leadership style.The technique used to draw the research sample was purposive sampling by giving a priority to the competent parties. The theory or leadership style used for the analysis was directive leadership style,supportive leadership style,participative leadership style,and work performancebased leadership style by Robert House.The research showed that the leadership of the head of the provincial Research and Development office of central sulawesi was successful.Furhermore,in getting the success,the styles used by the head of the Provincial research and Development Office of central participative in undertaking his leadership responsibilities.